Book Design as Tegel Information Media and Its History in Indonesia - Wantoro; Milega, Eldhie Rutfi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Many historic buildings have existed for a long time and still survive today. Strength and building materials and good maintenance are the keys to a strong historic building. One of the building materials that is often applied to historic buildings and has strong durability is tile or tegel. Tegel is a kind of tile made of cement and sand. Tegel have unique and distinctive characters, namely very attractive motifs and colors. However, along with the times and technology, tiles made manually have been eroded by the need for raw materials that can be produced quickly, such as ceramics. Indonesian people’s awareness of documentation is still low, especially regarding information on tile construction. In fact, it is very useful as information and reference for the next generation. So we need a way to inform tegel and their history in Indonesia. This study uses qualitative methods with sources from books, journals and articles as well as research to the public by distributing questionnaires. The designed information media is a book about tile information and its history in Indonesia. The book contains text supported by images and packaged in a classic style. The expected impact is that the younger generation who have an interest in the field of architecture and interiors, especially interest in tegel, can have in-depth knowledge and references.